The relationship between leadership style and turnover intention of nurses in the public hospitals of Jordan - Alkarabsheh O.H.M.; Jaaffar A.H.; Wei Fong P.; Attallah Almaaitah D.A.; Mohammad Alkharabsheh Z.H. (Cogent OA, 2023)
This study aimed to empirically determine the significant relationships between transformational leadership, authentic leadership and turnover intention among registered nurses (RNs) working in Jordanian public hospitals. This study deployed a quantitative cross-sectional survey using a questionnaire approach. From the 398 questionnaires distributed to the nine public hospitals in three regions in Jordan, there were 354 responses representing a response rate of 88.5%. The findings show that transformational leadership has a negative relationship with turnover intention. In addition, there was a negative relationship between authentic leadership and turnover intention among RNs in public hospitals in Jordan. The study results emphasised the roles of both leadership types in mitigating the turnover intention of RNs in Jordanian public hospitals. The stakeholders involved in the decision-making process should take note of these findings to develop effective strategies to retain nurses and other healthcare staff. 2022 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.